The Influence of The Effectiveness of The Internal Control System, Organizational Culture and Compliance with Legal Regulations on Fraud Detection - Awwalul Fajri, Nofal; Setiany, Erna (International Journal of Social Science, Education, Communication and Economics, 2024)
These results aim to make a scientific contribution to government accounting science, especially regarding fraud detection and efficiency levels which are influenced by the effectiveness of the internal control system, organizational culture and compliance with statutory regulations. It is hoped that the results of this research can be used as a reference for the Banten provincial government and school agencies as managers of budget funds in managing regional finances and can also make the Banten provincial government or school agencies more efficient than the previous year. The sample for this research was 36 high schools in the Tangerang City area. The research results show that the effectiveness of the internal control system has a positive and significant effect on fraud detection, the influence of organizational culture has a positive and significant effect on fraud detection, the influence of compliance with statutory regulations has a positive and significant effect on fraud detection, the effectiveness of the internal control system has a positive and significant effect on DEA, the influence of organizational culture has a negative and insignificant effect on DEA, and the influence of compliance with laws and regulations has a positive and significant effect on DEA.